Antibodies to Zic4 in paraneoplastic neurologic disorders and small-cell lung cancer - Bataller, L. (2004)
OBJECTIVE: To determine whether serum Zic4 antibodies associate with paraneoplastic neurologic disorders (PND) and small-cell lung cancer (SCLC), and the association of these antibodies with other onconeuronal immunities associated with SCLC. DESIGN/METHODS: The authors studied 498 patients (215 with PND and 283 without PND or without cancer). The presence of antibodies was tested with immunoblots of Zic4, HuD, and CRMP5 proteins. The tumor expression of these proteins was determined by immunohistochemistry. RESULTS: Zic4 antibodies were identified in 61 patients. Ninety-two percent of patients with Zic4 antibodies had SCLC; detection of these antibodies segregated with the presence of PND (p = 0.031). Intrathecal synthesis of Zic4 antibodies was demonstrated in 5/7 patients with PND. None of 175 control patients without PND or cancer had Zic4 antibodies. Because of the robust association between Zic autoimmunity and SCLC, all patients were tested for other SCLC-related antibodies; concurrent Zic4, Hu, or CRMP5 antibodies occurred in the serum or CSF of 27% of SCLC patients with PND. Patients with isolated Zic4 antibodies were more likely to develop predominant cerebellar dysfunction than patients with several immunities (p < 0.001). Tumors of patients with and without onconeuronal antibodies coexpressed Zic, Hu, and CRMP5 proteins, indicating that the tumor expression of these antigens is necessary, but not sufficient, for immunologic activation. CONCLUSIONS: In patients with neurologic symptoms of unknown cause detection of Zic4 antibodies predicts a neoplasm, usually a SCLC, and suggests that the neurologic disorder is paraneoplastic. Detection of Zic4 antibodies often associates with anti-Hu or CRMP5 antibodies. Patients with isolated Zic4 antibodies are more likely to develop cerebellar dysfunction than those with concurrent immunities.